Weight loss and carotid intima-media thickness—a meta-analysis - Skilton, M.; Yeo, S.; Ne, J.; Celermajer, D.; Caterson, I.; Lee, Crystal (Nature Publishing Group, 2017)
Objective: Obesity is a risk factor for clinical cardiovascular disease, putatively via increased burden of atherosclerosis. It remains contentious as to whether weight loss in people with obesity is accompanied by a reduction in intima-media thickness, a noninvasive marker of subclinical atherosclerosis, consistent with a lowering of risk of cardiovascular events. Methods: A systematic literature search was performed to identify all surgical and nonsurgical weight loss interventions that reported intima-media thickness. A meta-analysis was undertaken to obtain pooled estimates for change in intima-media thickness. Results: From the 3,197 articles screened, 9 studies were included in the meta-analysis, with a total of 393 participants who lost an average of 16 kg (95% CI 9.4–22.5) of body weight over an average follow-up of 20 months. The pooled mean change in carotid intima-media thickness was -0.03 mm (95% CI -0.05 to -0.01), which was similar between surgical and nonsurgical interventions. Conclusions: In people with obesity, weight loss was associated with a reduction in carotid intima-media thickness, consistent with a lowering in risk of cardiovascular events.